UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN KOOPERATIVE TIPE TIME TOKEN PADA SISWA KELAS II SDN 06 LUBUK JANTAN - Yusmawati, Erni (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes of Class II students of SDN 06 Lubuk Jantan in science subjects it was found that student learning outcomes in science subjects were still very low. The average student learning outcomes are still under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in sub-science subjects. Describe the coordination and sensory systems in humans and their relationship to health through the Time Token Cooperative Learning Model in Class II SDN 06 Lubuk Jantan Tanah Datar District. This research is a classroom action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 22 students in Class II SDN 06 Lubuk Jantan. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the Cooperative Learning Model Time Token Type can improve student learning outcomes in sub science subjects Identifying changes that occur in animal growth (in size) and plants (from seeds to plants). In SDN 06 Lubuk Jantan. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle were 52.84 (enough) to increase to 84.26 (Good) with an increase of 32.42%.